Bio-diversity, traditional knowledge and intellectual property: is sui generis the way forward for Malaysia? - Abdul Ghani Azmi, Ida Madieha (2010)
One of the obligations set under the Convention on Biological Diversity is the protection of the rights and knowledge of indigenous and local communities. This has been the issue that has been explored at various international forums such as CBD COP, WIPO's IGC and WTO, FAO, UNCTAD, UNHCHR and WHO. Issues being investigated include access to genetic resources; benefit sharing options, biodiversity, traditional medicine and rights of the indigenous peoples.